Influence of Sex and Management System on Seroprevalence of Newcastle Disease Antibodies in Indigenous Chicken in Ashanti Region, Ghana (African Journal of Biomedical Research, 2020)
This study sought to provide data on influence of sex and management system on seroprevalence of Newcastle disease (ND) in unvaccinated indigenous chicken in Ashanti Region, Ghana. A total of seventy-one (71) local chickens were screened for ND virus antibodies using haemagglutination inhibition (HI) test. The overall seroprevalence of 69.0% was obtained. A higher ND antibodies seroprevalence of 60.56% was recorded in local chicken at Aboaso (kept under extensive system) than those from Amakom (kept under intensive system) with 8.45%.  . More female birds from extensive system (11 (69.1%) tested positive for the ND antibodies also a higher mean titer of 6.4 were obtained in positive male birds also the same system. The differences in seroprevalence with respect to management systems and the mean titre values with respect to sex of birds were statistically significant (p
Keywords: Newcastle disease; seroprevalence; indigenous chicken; Management systems; Ghana